F41 pili as protective antigens of enterotoxigenic Escherichia coli that produce F41, K99, or both pilus antigens. - Runnels, P L (1987)
Pigs suckling dams that have been vaccinated with pilus antigen are protected against challenge with enterotoxigenic Escherichia coli (ETEC) strains that express the same pilus antigen. However, some ETEC strains express more than one pilus antigen. Pregnant swine were vaccinated either with E. coli HB101 that harbored a recombinant plasmid coding for F41 expression (F41+) or with the HB101 parent strain that carries the pHC79 vector (F41-). Suckling pigs born to vaccinated dams were challenged with ETEC that expressed either K99, F41, or both pilus antigens. Production of F41 in vivo was demonstrated by immunofluorescence assay of sections of ileum and by seroconversion against F41 antigen by pigs challenged with F41+ and K99+ F41+ ETEC strains. The F41+ vaccine protected against challenge with an F41+ ETEC strain. In contrast, F41+ vaccination did not protect against challenge with K99+ or K99+ F41+ ETEC strains. The F41- vaccine did not protect against challenge with any strain used. The results indicate that K99+ F41+ ETEC strains produce F41 antigen in the small intestine during disease and that F41+ vaccination can be a protective antigen if the challenge strain expresses only F41 antigen, but that F41+ vaccination may not protect against strains that produce both K99 and F41 antigens.